2023
DOI: 10.1002/pts.2737
|View full text |Cite
|
Sign up to set email alerts
|

Review of packaging for improving storage quality of fresh edible mushrooms

Abstract: Edible mushrooms are favoured by people for their rich nutrition, medicinal value and unique flavour. The quality of postharvest mushroom decreased sharply because of its special tissue structure and physiological characteristics. Compared with other preservation technologies, packaging has been widely used in the preservation of mushrooms because of its strong preservation effect, green and convenient characteristic. This review discussed the quality deterioration of fresh mushrooms and its influencing factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 127 publications
0
11
0
Order By: Relevance
“…Desirable techno-functional properties of packaging materials such as permeability and mechanical and thermal properties [44] play a key role in maintaining quality by preventing off-flavour development, contamination, browning, and softening, thereby extending the shelf life of mushrooms [29,45]. Studies have shown that modified atmosphere packaging (MAP) stands first in terms of frequency of use for edible mushrooms, followed by active packaging, biodegradable film packaging, and nanopackaging systems based on a review of 235 articles on mushroom preservation techniques published between 2010 and 2021 [29] (Figure 1).…”
Section: Mechanisms Of Action and Preservation Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Desirable techno-functional properties of packaging materials such as permeability and mechanical and thermal properties [44] play a key role in maintaining quality by preventing off-flavour development, contamination, browning, and softening, thereby extending the shelf life of mushrooms [29,45]. Studies have shown that modified atmosphere packaging (MAP) stands first in terms of frequency of use for edible mushrooms, followed by active packaging, biodegradable film packaging, and nanopackaging systems based on a review of 235 articles on mushroom preservation techniques published between 2010 and 2021 [29] (Figure 1).…”
Section: Mechanisms Of Action and Preservation Effectsmentioning
confidence: 99%
“…Nanopackaging minimizes tissue aging, electrical conductivity, and the accumulation of reactive oxygen species (ROS) by controlling the energy metabolism and enzymatic activity of mushrooms [29]. MAP lowers the rate of respiratory metabolism, thereby reducing the loss of cell wall components and cell swelling [62].…”
Section: Changes In Quality Of Fresh Mushroomsmentioning
confidence: 99%
See 3 more Smart Citations